2011
DOI: 10.1007/s11434-011-4513-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the spread of nuclear radiation from the damaged Fukushima Nuclear Power Plant

Abstract: Japan suffered a M9.0 earthquake and massive tsunami on March 11, 2011, which seriously damaged the Fukushima Nuclear Power Plant and caused a nuclear crisis. The spread of nuclear radiation from the power plant through the atmosphere and ocean was predicted with a short-term climate forecasting model and an ocean circulation model under some idealized assumptions. If nuclear matter were leaked in the near-ground layer of 992 hPa, the climate model results show that the nuclear radiation would cover North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…Iodine-131 was first reported in Thessaloniki, Northern Greece on March 26, 2011 (Manolopoulou, et al, 2011). Based on the atmospheric circulation model in the near-ground layer (992 hPa), Qiao et al (2011) predicted that a radioactive cloud would have arrived in China 20 d after the initial release of radioactive material from the Fukushima accident site. Takemura et al (2011) reported a numerical simulation of global transport of atmospheric particles emitted from the Fukushima Dai-ichi Nuclear Power Plant.…”
Section: Resultsmentioning
confidence: 99%
“…Iodine-131 was first reported in Thessaloniki, Northern Greece on March 26, 2011 (Manolopoulou, et al, 2011). Based on the atmospheric circulation model in the near-ground layer (992 hPa), Qiao et al (2011) predicted that a radioactive cloud would have arrived in China 20 d after the initial release of radioactive material from the Fukushima accident site. Takemura et al (2011) reported a numerical simulation of global transport of atmospheric particles emitted from the Fukushima Dai-ichi Nuclear Power Plant.…”
Section: Resultsmentioning
confidence: 99%
“…More volatile and/or particulate bound isotopes and radionuclides were transported across the Pacific towards the North American continent and around the northern hemisphere (CTBTO, 2011;Takemura et al, 2011;Qiao et al, 2011). Traces of contaminated air masses were detected in most of European countries despite dispersion and washout along the trip of the contaminated air masses (Masson et al, 2011;Pittauerová et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have studied numerical simulations of radionuclides from the Fukushima NPP by the above mentioned models, such as Tsumune et al (2012) who employed ROMS to simulate the circulation of the Northeast Pacific Ocean and assess the concentration of radionuclides; Behrens et al (2012) estimated the long-term dispersion after Fukushima nuclear crisis; Qiao et al (2011) estimated the spread of nuclear radiation and predicted the time to spread to Europe and America. Note that most of them focused merely on the dispersion of contaminants, while the radioactive impacts of the contaminated water are less studied.…”
mentioning
confidence: 99%